2015
DOI: 10.18671/scifor.v43n108.24
|View full text |Cite
|
Sign up to set email alerts
|

Otimização do processo de extração taninos de Pinus oocarpa para manufatura de adesivos para madeira

Abstract: Esse trabalho teve por objetivo verificar a influência da temperatura e do teor de sal extrator na extração de taninos condensáveis da casca de Pinus oocarpa para o uso na colagem da madeira. Um experimento fatorial composto por três níveis de temperatura (60°C, 80°C, 100°C) e 4 níveis de concentração de sulfito de sódio (0%, 1%, 3%, 5%) foi utilizado. A determinação das propriedades dos extratos tânicos foi realizada através da obtenção dos teores de polifenóis condensados pelo método de Stiasny (Número de St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
0
0
2
Order By: Relevance
“…Based on these yields, the additions of the extracting agents (through hydrolysis and sulfitation) promoted significant increases in the extraction of solid tannin fractions from the MT bark. Some previous studies also found similar results using other extracting agents [2,13,[40][41][42]. In the present study, the EYc values can be mainly attributed to the use of basic hydrolysis (NaOH) and sulfitation (NaHSO3).…”
Section: Powder Extract Yieldssupporting
confidence: 86%
“…Based on these yields, the additions of the extracting agents (through hydrolysis and sulfitation) promoted significant increases in the extraction of solid tannin fractions from the MT bark. Some previous studies also found similar results using other extracting agents [2,13,[40][41][42]. In the present study, the EYc values can be mainly attributed to the use of basic hydrolysis (NaOH) and sulfitation (NaHSO3).…”
Section: Powder Extract Yieldssupporting
confidence: 86%
“…O percentual de tanino condensado contido nos extratos ou número de Stiasny (NS) foi determinado pela razão entre a massa de tanino e a massa dos extrativos totais extrapolada para 50 mL e o resultado convertido em porcentagem, segundo a equação 1. 15 (%) = massa de tanino massa de extrativos totais 100 (Eq. 1)…”
Section: Determinação Do Teor De Tanino Pelo Método De Stiasnyunclassified
“…Cada especie vegetal se comporta de modo diferente en relación con el rendimiento y calidad de los taninos, los cuales están asociados a la forma de extracción, esta puede ser con agua (Trugilho et al, 1997), sulfito de sodio (Carvalho et al, 2014a;Tahir et al, 2002;Vieira et al, 2011), bisulfito de sodio, sulfato y carbonato de sodio (Santiago et al, 2019), metabisulfito e hidróxido de sodio (Vázquez et al, 2001). Este proceso puede ser realizado aplicando diferentes temperaturas de acuerdo con lo indicado en diferentes investigaciones desarrolladas por Vieira et al (2014), Rodrigues et al (2015), Nath et al (2017), Sartori et al (2018) y Medeiros et al (2018). Existen pocos estudios relacionados con la extracción de taninos a partir de la corteza de pino mediante termomodificación.…”
Section: Introductionunclassified